2019
DOI: 10.1038/s41598-019-51805-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in Fabry Disease

Abstract: Fabry disease is an X-linked deficiency of the lysosomal hydrolase alpha-galactosidase A (alpha-Gal).This results in an accumulation of globotriaosylceramide (GL-3/Gb3) in a variety of cells with subsequent functional impairment. The continuous progress of FD often leads to decreased quality of life and premature death caused by multi-organic complications. The overall aim of our study was to determine the amount of circulating miRNAs in Fabry patients and to test whether ERT would alter the level of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The circulating miR199a-5p and miR-126-3p are upregulated in Fabry patients, which can be normalized in Fabry patients after ERT [ 118 ]. To further determine whether ERT alters the level of circulating miRNAs in Fabry patients, Xiao et al performed the microRNA sequencing for the serum samples from Fabry patients with or without ERT [ 119 ]. A total of 145 miRNAs are identified to be regulated by ERT.…”
Section: Mirnas In Fabry Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The circulating miR199a-5p and miR-126-3p are upregulated in Fabry patients, which can be normalized in Fabry patients after ERT [ 118 ]. To further determine whether ERT alters the level of circulating miRNAs in Fabry patients, Xiao et al performed the microRNA sequencing for the serum samples from Fabry patients with or without ERT [ 119 ]. A total of 145 miRNAs are identified to be regulated by ERT.…”
Section: Mirnas In Fabry Diseasementioning
confidence: 99%
“…A total of 145 miRNAs are identified to be regulated by ERT. Among those miRNAs, miR-1307-5p, miR-21-5p, miR-152-5p and miR-26a-5p were confirmed to be downregulated in the serum of Fabry patients after ERT in a validation cohort [ 119 ]. These studies suggested that urinary and circulating miRNAs might be used as biomarkers to assess the disease progression and the efficacy of ERT in Fabry patients.…”
Section: Mirnas In Fabry Diseasementioning
confidence: 99%
“…In serum, specific miRNAs species, namely, miR-1307-5p, miR-21-5p, miR-152-5p, and miR-26a-5p, were significantly down-regulated in Fabry patients with ERT, compared to those without. Additionally, miR-19a-3p and miR-486-5p were reported to be down-regulated only in male patients with ERT [82]. The analysis of miRNA expression is not commonly used in the clinical practice, due to the lack of standardized protocols.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…The pathways that were investigated were axon guidance signalling pathways and the TGF-beta signalling pathway, which were found to be targets of miRNAs. It was reported that abnormal regulation of miRNAs resulted in changes in axon guidance pathways: this effect may contribute to neurological processes leading to neurological manifestations in Fabry disease [79].…”
Section: Micrornasmentioning
confidence: 99%